2016
DOI: 10.1186/s12943-016-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 induces docetaxel resistance in prostate cancer by targeting SEC23A and YAP1

Abstract: BackgroundTreatment options for metastatic castrate-resistant prostate cancer (mCRPC) are limited and typically are centered on docetaxel-based chemotherapy. We previously reported that elevated miR-375 levels were significantly associated with poor overall survival of mCRPC patients. In this study, we evaluated if miR-375 induced chemo-resistance to docetaxel through regulating target genes associated with drug resistance.MethodsWe first compared miR-375 expression level between prostate cancer tissues and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 31 publications
4
111
0
2
Order By: Relevance
“…Moreover, its occurrence and recurrence rates had been significantly increasing both in developing and developed countries. [1][2][3][4] Androgen deprivation therapy (ADT) first proposed by Charles Huggins et al on their seminal observations is highly effective in controlling metastatic prostate cancer. 5 Although ADT is effective for some patients, most patients may develop castration resistance PCa (CRPC).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its occurrence and recurrence rates had been significantly increasing both in developing and developed countries. [1][2][3][4] Androgen deprivation therapy (ADT) first proposed by Charles Huggins et al on their seminal observations is highly effective in controlling metastatic prostate cancer. 5 Although ADT is effective for some patients, most patients may develop castration resistance PCa (CRPC).…”
Section: Introductionmentioning
confidence: 99%
“…10,13,14 Our previous study showed that miR-375 can obstruct HCC progression in mice by suppressing yes-associated protein 1 (YAP1) and astrocyte elevated gene-1 (AEG-1). 15 Moreover, AEG-1 has been shown to play a pivotal role in chemoresistance in human HCC, neuroblastoma, and breast cancer. [15][16][17][18] In cancer cells, AEG-1 promotes the expression of MDR1, resulting in increased efflux and decreased accumulation of chemotherapeutics, which leads to drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, AEG-1 has been shown to play a pivotal role in chemoresistance in human HCC, neuroblastoma, and breast cancer. [15][16][17][18] In cancer cells, AEG-1 promotes the expression of MDR1, resulting in increased efflux and decreased accumulation of chemotherapeutics, which leads to drug resistance. 19,20 The molecular mechanism underlying this process includes facilitation of the association of MDR1 mRNA with polysomes by AEG-1, resulting in increased translation of MDR1 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researches also show that miR-375 exerts effect on the sensitivity of tumor treatments. For example, miR-375 is reported to be involved in development of chemoresistance of multiple tumor cells, such as prostate cancer, breast cancer, pancreatic cancer and gastric cancer [28-31], suggesting that miR-375 might serve as potential predictive biomarkers to chemotherapy and/or therapeutic targets to overcome chemoresistance in human cancers. Meanwhile, the correlation of miR-375 with radiosensitivity of tumor cells is also reported.…”
Section: Discussionmentioning
confidence: 99%